Tropical cyclone kinetic energy and structure evolution in the HWRFx model - Maclay, Katherine S., author; Vonder Haar, Thomas, advisor; DeMaria, Mark, advisor; Schubert, Wayne, committee member; Schumacher, Russ, committee member; Krueger, David, committee member (Colorado State University. Libraries, 2011)
Tropical cyclones exhibit significant variability in their structure, especially in terms of size and asymmetric structures. The variations can influence subsequent evolution in the storm as well as its environmental impacts and play an important role in forecasting. This study uses the Hurricane Weather Research and Forecasting Experimental System (HWRFx) to investigate the horizontal and vertical structure of tropical cyclones. Five real data HWRFx model simulations from the 2005 Atlantic tropical cyclone season (two of Hurricanes Emily and Wilma, and one of Hurricane Katrina) are used. Horizontal structure is investigated via several methods: the decomposition of the integrated kinetic energy field into wavenumber space, composite analysis of the wind fields, and azimuthal wavenumber decomposition of the tangential wind field. Additionally, a spatial and temporal decomposition of the vorticity field to study the vortex Rossby wave contribution to storm asymmetries with an emphasis on azimuthal wavenumber-2 features is completed. Spectral decomposition shows that the average low level kinetic energy in azimuthal wavenumbers 0, 1 and 2 are 92%, 6%, and 1.5% of the total kinetic energy. The kinetic energy in higher wavenumbers is much smaller. Analysis also shows that the low level kinetic energy wavenumber 1 and 2 components can vary between 0.3-36.3% and 0.1-14.1% of the total kinetic energy, respectively. The asymmetries associated with storm motion, environmental shear, and the relative orientation of these vectors are examined. A composite analysis shows a dominant wavenumber-1 asymmetry associated with the storm motion and shear vectors. For storm motion the asymmetry is located in the right front quadrant relative to the motion vector with a magnitude exceeding 2.5 m/s, and for shear the asymmetry is located 90⁰ left of the shear vector with a magnitude exceeding 5 m/s. The locations of these wavenumber-1 asymmetries are consistent with the findings of previous studies. Further composite analysis of the asymmetries associated with the relative orientation of the storm motion and shear vectors reveals that when the vectors are aligned versus opposed the wavenumber-1 asymmetries have roughly equivalent magnitude but very different azimuthal location (when aligned the maximum is located in the left front quadrant relative to the storm motion, and when opposed is located nearly 90⁰ to the right of the storm motion). The magnitude of the wavenumber-2 asymmetries is much larger when the storm motion and shear vectors are aligned (exceeding 2.5 m/s) than when they are opposed (~0.5 m/s). The results indicate that shear induced asymmetries extend more deeply through the troposphere than storm motion induced asymmetries. Furthermore, the vortex Rossby wave analysis provides compelling evidence to support their existence and their contribution to the wavenumber-2 asymmetries in the simulated storms. The vertical structure is studied in terms of the relationship between the size of the radius of maximum wind and its slope, and whether the radius of maximum wind is well approximated by a constant absolute angular momentum surface. The impacts of environmental shear on these relationships are specifically examined. While there is some evidence to suggest that moderate shear can have a constructive influence on the storm, the relationships between the radius of maximum wind and its slope, and the slopes of the radius of maximum wind and the constant absolute angular momentum surface deteriorate quickly with increasing shear. The vertical warm core structure of the tropical cyclones is investigated in terms of the height and magnitude of the primary and any possible secondary warm core features (as measured in terms of the temperature anomalies). The purpose of this analysis is to determine the general warm core structure and establish if there are any significant trends with respect to storm evolution, environmental shear, or storm intensity change. It is determined that there is often a dual warm core structure with a primary warm anomaly located in the 5-10 km height region with a magnitude generally between 5-10 K and a secondary warm anomaly located either below 5 km or in the 16-19 km region of lesser magnitude. The height and magnitude of the primary warm core is not found to be linked to the environmental shear and is weakly correlated to the 6 h averaged intensity change. Finally, the cold pool structure of the storms is briefly examined. The simulated storms exhibit persistent cold pockets at low levels that are likely related to evaporation of rain. An investigation of whether these cold pockets are enhanced in association with extratropical transition processes reveals a notable decrease in the low level cold anomalies for the simulation experiencing extratropical transition.